Agathas Mystery : The Night in Question - Book 2 - Glasgow, Kathleen, 1969-; Lawson, Liz, 1980- (New York : Delacorte Press, 2023)
When Iris and Alice's high school dance at the infamous Levy Castle, the site of starlet Mona Moody's unsolved death in the 1940s, is interrupted by a violent assault, they pull out their murder boards and get back to work.
Keywords: High schools -- Juvenile fiction; Schools -- Juvenile fiction; Dance -- Juvenile fiction; High schools -- Fiction; Schools -- Fiction; Dance -- Fiction; Mystery and detective stories; Detective and mystery fiction; Novels